Digital transformation and innovation of the European SMEs. How Romania replies to the digitalization phenomena? - Emilia JERCAN; Teodora NACU (Theoretical and Applied Economics, 2024)

(untitled)
Digital technologies and digitalization represent a growing trend across countries in Europe, especially for developed economies and markets. Today, it is commonly acknowledged that an important factor for the SMEs’ competitiveness, growth, and success, is the implementation of digital innovation and new tools. The varied and multidimensional reasons that either help or prevent SMEs from adopting digital tools and innovation, nevertheless, are numerous, and the ability of SMEs in Europe to obtain digital advancement and innovation is examined in this paper in relation to the influence of external factors such as governmental policies. By analysing different governmental policies among the EU, the aim of this paper is to establish a connection between various regulations and the innovation performance of Romanian SMEs.